Interaction of Islamic Economics and Government Transformation Technology in Indonesian Muslim Society - Indriana, Indriana; Arman, Arman; Yussof, Ishak; Maasi, Jenneke Widya (Jurnal Ilmiah Al-Syir'ah, 2023)
The interaction of Islamic economics and government transformation Technology in Indonesian Muslim society can create justice, prosperity for all parties, and blessings both in this world and the hereafter, to know the interaction of Islamic economics and government transformation Technology in Indonesian Muslim society. The research method uses a quantitative survey approach to ensure accuracy and relevance in this research. The type of data used is primary data using a sampling technique via snowball sampling using an online survey. With locations in 16 provinces in Indonesia: South Sulawesi, West Java, East Java, DKI Jakarta, Nanggroe Aceh Darussalam, North Sumatra, Gorontalo, South Sumatra, East Kalimantan, North Maluku, West Kalimantan, Riau, West Papua, Bali, Papua, and East Nusa Tenggara, it can see that the largest is DKI Jakarta and the lowest is West Papua, with several 1200 informants in each province, 75 informants with a period of 2 years. The technique used to collect study data on published material in the interaction between Islamic economics and government transformation technology is that Islamic economics is based on Islamic ethical principles such as the prohibition of usury (interest), justice, and fair distribution. In Indonesian Muslim society, these principles can be used as a guide in business and finance, and advances in technology, especially the internet and digital platforms, have provided greater access for society to participate in the economy and governance, with Islamic economics encouraging entrepreneurship. Interaction between Islamic economics and technology has great potential to shape Indonesia's economic, social, and governmental future in a way that is more in line with social justice.